Cardiac Safety of (Neo)Adjuvant Trastuzumab in the Community Setting: A Single-Center Experience - da Fonseca, Leonardo Gomes (S. Karger GmbH, 2014)
BACKGROUND: Trastuzumab improves the survival of patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer (BC). The incidence and long-term impact of trastuzumab-related cardiotoxicity in the community setting is of great clinical importance. MATERIAL AND METHODS: Patients with HER2-positive BC treated with (neo)adjuvant trastuzumab were retrospectively evaluated. Cardiotoxicity was defined as cardiac death or absolute decrease in left ventricular ejection fraction of at least 10% to a value less than 50%, or symptomatic heart failure. RESULTS: We evaluated 237 patients: median age 53 years (range 27–83 years). 40.5% of these patients had received neoadjuvant and 59.5% adjuvant chemotherapy. The majority (83.9%) were treated with an anthracycline-based regimen. Median exposure to trastuzumab was 8 months (range 2–12 months). Cardiotoxicity was diagnosed in 20.2%, but symptoms only occurred in 3.8%. 41.6% recovered cardiac function. None of the risk factors were associated with cardiotoxicity. CONCLUSION: The incidence of trastuzumab-related cardiotoxicity found in this study was slightly higher than those reported in randomized clinical trials. Nevertheless, most patients were asymptomatic. We describe the cardiac outcomes of a non-selected population, which possibly reflects those found in the ‘real world’. The risks versus benefits of trastuzumab use remain in favor of treatment, but cardiotoxicity should be monitored.